MORPHOLOGY AND SYNTAX AND CROSSLINGUISTIC FINDINGS IN NEUROLINGUISTICS - Muqаddаm Аbdug'оfur qizi Jurаyevа; Mirzarahimov Mirzohid Alisher o’g’li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
In this article disturbances especially agrammarism and other aphasic disorders are enlightened with correlation morphology. Agrammatism has been the main object of studies of grammar and aphasia and shed on the light the relationship between comprehension and production. Some syntactic phenomena characterizing aphasia are listed.